Readiness, Access, Challenges, and Efficiency in using Flexible Mode of Learning: Inputs for Instructional Management Plan - Geronimo, Cecilia A.; Geronimo, Audie L.; Faustino, Sarah M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
The objective of the study is to determine the readiness, access, challenges, and efficiency in using the Flexible Mode of Learning among the faculty members and students of the College of Engineering in a Higher Education Institution in the academic year of 2020-2021. The study used a descriptive research design, constructed, and submitted for validation the survey questionnaires, and distributed google forms. and utilized mixed methods of research. The results of the study show that in terms of readiness, most of the faculty members attended the training webinars on a flexible mode of learning; spent more time attending the webinars; few have sufficient resources, but the majority are technically capable and prefer the blended learning modality. While the student-respondents, more than half of the respondents did not attend the training webinars, and minimal time was spent, the majority have sufficient resources, are technically capable, and preferred the blended learning modality. In terms of access, both faculty members and students use Wi-Fi connection and use devices like the combination of computers and smartphone/tablet; but differ in the time spent per day and per week on blended learning. The faculty members and students perceived that the level of efficiency of the flexible mode of learning implementation is moderately efficient. The challenges encountered by faculty members were the attitude of their students towards their subjects while the students are on their preparedness on the subjects, physical environment, financial and poor internet connection. The researchers proposed an instructional management plan based on the results of the study.